Geophysical Characteristic and Water Resources Availability in Rote Ndao, East Nusa Tenggara as a Basic for Coastal Tourism Development - Tamelan, Paul Gabriel (Journal of Indonesian Tourism and Development Studies, 2015)
East Nusa Tenggara has been known as an arid region in Indonesia. Water scarcity is among the crucial problems in East Nusa Tenggara. Recently, however, some area in East Nusa Tenggara has been developed as tourism area which is important for local economic development. Lands and water conservation therefore becomes the crucial issues in East Nusa Tenggara. The aims of the study are to indentify and describes the recent geophysical characteristics of land in Rote Ndao as a basic factor for water conservation and sustainable tourism development in arid environments. Field work and secondary data collection were done in Rote Ndao Regency, East Nusa Tenggara. Result of the study confirm that climates and rainfall was limited, but in some month there are heavy rain. Absent of land conservation strategy lead to the rapid runoff. The topography was undulating and if it is properly managed such structure can be used to support water conservation. Vegetation covers and quality was limited and it is becomes the barrier for water infiltration to soils. Therefore, the re-vegetation programs should be promoted widey in the island. It is especially important to enhance the susutainable coastal tourism destination in Rote Ndao. Keywords: arid environment, soil conservation, tourism, water management